Delirium and effect of circadian light in the intensive care unit: a retrospective cohort study. Issue 3 (17th November 2017) - Estrup, S.; Kjer, C. K. W.; Poulsen, L. M.; Gøgenur, I.; Mathiesen, O.
Abstract : Background: Delirium is a serious condition often experienced by critically ill patients in intensive care units (ICUs). The role of circadian light for this condition is unclear. The aim of this study was to describe incidence of delirium, risk factors for delirium, and the association between delirium and circadian light for patients in the ICU. Methods: This is a retrospective cohort study of all patients at a Danish ICU from 1 August 2015 to 31 January 2016. Exclusion criteria were heavy sedation, no Confusion Assessment Method for the ICU (CAM‐ICU) scores, or inability to communicate in Danish. Delirium was defined as at least one positive CAM‐ICU score or treatment with haloperidol. Three of nine beds at the ICU had a circadian light installation. Allocation to ICU beds with or without circadian light depended on availability at admission. Risk factors for development of delirium were analyzed by simple and multiple logistic regression. Results: We included 183 patients in the study. The incidence of delirium was 28% (95% CI 22, 35). Allocation to beds with or without circadian lighting was not associated with delirium incidence (OR 1.14; 95% CI 0.55, 2.37; P = 0.73). We found that Simplified Acute Physiology Score II (SAPS II) (OR 1.03; 95% CI 1.01, 1.06; P = 0.002), and dexmedetomidine was associated with delirium (OR 4.14; 95% CI 1.72, 10.03; P = 0.002). Conclusion: In this population of patients admitted to an ICU during 6 months, the incidence of delirium was 28%. We did not find an association between circadian light and development of delirium.